Analysis of Sustainable Energy and Environmental Policies in Agriculture in the EU Regarding the European Green Deal - Ioan Prigoreanu; Bianca Antonela Ungureanu; George Ungureanu; Gabriela Ignat (Energies)
The paper analyzes energy and environmental policies in agriculture in the context of the European Green Deal, emphasizing the contribution of the Common Agricultural Policy in supporting sustainability objectives. The study explores how Member States implement specific measures to reduce greenhouse gas emissions, conserve natural resources, and protect biodiversity by 2030. The analysis focuses on three main objectives: reducing emissions and adapting to climate and energy changes, managing natural resources sustainably and ensuring energy efficiency, and promoting organic farming and conserving biodiversity. Using a methodology that aligns Green Deal goals with CAP measures, this research involves a comparative analysis between Member States, highlighting disparities in policy implementation, particularly between Eastern and Western Europe, suggesting that a coordinated EU approach is needed to support equitable progress. The paper provides a detailed perspective on the progress made and offers recommendations for harmonizing agricultural policies in the EU, supporting farmers in adopting ecological and energy efficient practices, and ensuring a consistent approach in achieving Green Deal objectives by 2030.